2015
DOI: 10.1002/aoc.3365
|View full text |Cite
|
Sign up to set email alerts
|

Room‐temperature Suzuki–Miyauracross‐coupling reaction with α‐diimine Pd(II) catalysts

Abstract: An α‐diimine Pd(II) complex containing chiral sec‐phenethyl groups, {bis[N,N′‐(4‐methyl‐2‐sec‐phenethylphenyl)imino]‐2,3‐butadiene}dichloropalladium (rac‐C1), was synthesized and characterized. rac‐C1 was applied as an efficient catalyst for the Suzuki–Miyaura cross‐coupling reaction between various aniline halides and arylboronic acid in PEG‐400–H2O at room temperature. Among a series of aniline halides, rac‐C1 did not catalyze the cross‐coupling of aniline chlorides and fluorides but efficiently catalyzed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 36 publications
(54 reference statements)
0
11
0
Order By: Relevance
“…Formic acid (0.2 ml) was added to a stirred solution of 2,3‐butanedione (0.17 g, 2.00 mmol) and 2,6‐diisopropyl‐4‐phenylaniline (1.01 g, 4.00 mmol) in MeOH (35 ml). The mixture was refluxed for 12 h, and then cooled, and the precipitate was separated by filtration.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Formic acid (0.2 ml) was added to a stirred solution of 2,3‐butanedione (0.17 g, 2.00 mmol) and 2,6‐diisopropyl‐4‐phenylaniline (1.01 g, 4.00 mmol) in MeOH (35 ml). The mixture was refluxed for 12 h, and then cooled, and the precipitate was separated by filtration.…”
Section: Methodsmentioning
confidence: 99%
“…Dichloromethane, toluene, tetrahydrofuran and hexanes were purified by solvent purification systems. All para ‐phenylaniline derivatives and complexes 5 were prepared according to reported procedures. All other reagents were purchased from commercial sources and used without purification.…”
Section: Methodsmentioning
confidence: 99%
“…We have previously reported that bulky ortho‐sec‐ phenethyl ‐ substituted and ortho‐ phenyl substituted α‐ diimine nickel and palladium complexes exhibited high activities toward ethylene polymerization and produced highly branched polyethylene upon activation with Et 2 AlCl or MMAO, and also produced branched poly(1‐alkene)s with high molecular weight. We anticipated that bulky α‐ diimine ligands might control chain walking and produce regioregular polymers.…”
Section: Introductionmentioning
confidence: 99%
“…A solution of 2,3‐butanedione (0.17 g, 2.00 mmol), 2‐ethyl‐6‐methy ‐ 4 ‐ phenylaniline (0.84 g, 4.00 mmol), and formic acid (0.2 ml) in MeOH (35 mL) was heated to reflux for 12 h. The mixture was cooled, and the precipitate was separated by filtration. The yellow solid was washed with cold ethanol and dried under vacuum (0.71 g, 75% yield).…”
Section: Methodsmentioning
confidence: 99%